Scenario of Neonatal Respiratory Distress in Tertiary Hospital - Rijal, Prashant; Shrestha, Mandira (Journal of Nepal Health Research Council, 2018)
Background: Respiratory distress is one of the most common reasons for admission in Neonatal Intensive Care Unit. However, studies of newborn admitted with respiratory distress in our setup are limited. This study aims to look for incidence of neonatal respiratory distress in our setup, to analyze the common causes of respiratory distress and to determine possible strategic plan needed for better clinical outcome. Methods: A cross sectional study was conducted from March 2013 to December 2014 in Nepal Medical College and Teaching Hospital. Data of all the neonates with respiratory distress admitted during this period were analyzed. Results: Total 317 (13.4%) neonates were admitted to Neonatal Intensive Care Unit during the study period.109 neonates developed respiratory distress comprising 34.3% of all Neonatal Intensive Care Unit admissions. Incidence of neonatal respiratory distress was 4.6%. The common causes of respiratory distress in our study were meconium aspiration syndrome in 21.1%, septicemia in 16.5%, transient tachypnea of newborn in 15.5%, pneumonia in 14.6%, birth asphyxia and hyaline membrane disease were in each 11.9% of the neonates. Caesarean section was the most common predisposing factor associated with the development of transient tachypnea of newborn in 82.3% newborns (p=.001). The overall mortality rate due to respiratory distress was 12.8%. Conclusions: Meconium aspiration syndrome, septicemia and hyaline membrane disease are the most important causes of respiratory distress in our setup. Good obstetric care, proper training of health care personnel in neonatal resuscitation and early recognition of potential risk factors of respiratory distress will be helpful. Keywords: Meconium aspiration syndrome; neonatal period; respiratory distress